The idea of labour law - Davidov, Guy, 1970-; Langille, Brian (Oxford : Oxford University Press, 2011)
There is growing interest in trying to understand and rethink the goals of labour law in light of changing realities in the labour market and regulation. Responding to such fundamental questions as: What is labour law for? How can it be justified? And on what should reforms be based? this book challenges the way we think about labour law.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Labor laws and legislation